The meanings of authenticity in early childhood education: A systematic review - Bin Wu; Sarah Callahan; Maryanne Pale; Wendy Goff (Social Sciences and Humanities Open)
Since the 1990s, the term “authenticity” has been increasingly used in the research literature. Its meanings and dimensions are manifold, encompassing diverse epistemological standpoints, yet are seldom explicitly defined. Focusing on early childhood education (birth-8), this systematic review of 148 papers published between 1990 and 2022, aims to 1) understand the meanings of authenticity in the existing literature and 2) propose a theoretical matrix for mapping the dimensions of authenticity across different constructs. The proposed matrix provides a shared platform for comparing and scrutinising different interpretations of the concept of authenticity. The review shows that, despite its varied meanings and dimensions, authenticity is consistently constructed along two continuous axes: one between the tensions of the inner/self and external factors/others, and the other between conformation and transformation. The proposed matrix connects different schools of thought on authenticity, offering a shared platform that supports critical debate while recognising the concept's diverse interpretations and applications.